2019
DOI: 10.2217/imt-2018-0118
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity with Immune System Targeting Drugs: A Meta-Analysis of Anti-PD/PD-L1 Immunotherapy Randomized Clinical Trials

Abstract: Background: With antiprogrammed death receptor-1 (anti-PD-L1) therapy, a recent meta-analysis reported higher incidence of cutaneous, endocrine and gastrointestinal complications especially with dual anti-PD-L1 immunotherapy (IMM). Methods: Our primary outcome was assessment of all cardiotoxicity grades in IMM compared with different treatments, thus a systemic review and a meta-analysis on randomized clinical trials (RCTs) were done. Results: We included 11 RCTs with 6574 patients (3234 patients in IMM arm vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…And it has been implicated in evading immune surveillance (Janji et al, 2016). Thus, can be related to various predictive and prognostic markers Abdel Karim et al, 2018;Magdy et al, 2018Rahouma et al, 2019). However, these studies have always been in vitro experiments or done using murine models.…”
Section: Discussionmentioning
confidence: 99%
“…And it has been implicated in evading immune surveillance (Janji et al, 2016). Thus, can be related to various predictive and prognostic markers Abdel Karim et al, 2018;Magdy et al, 2018Rahouma et al, 2019). However, these studies have always been in vitro experiments or done using murine models.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of PD-1 and PD-L1 inhibitors involves mainly restarting the T cell-mediated tumor cell death process; at the same time, interferes with the normal immune system. In a meta-analysis, the authors divided patients into NSCLC group and other cancer groups (melanoma, prostate cancer), that is, based on the cancer types and indicated that PD-1/PD-L1 inhibitors have no significant differences in cardiotoxicity compared with chemotherapy or placebo [ 25 ] . However, since the search date was limited to February 2017, only 3 studies of NSCLC were included.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent meta-analysis, the findings showed no marked differences in cardiotoxicity between immunotherapy and chemotherapy. [ 25 ] This is because individual adverse cardiac events were not analyzed, and only 3 clinical trials were included with the retrieval date set for February 2017. In recent years, several clinical trials have been conducted and results published in peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is again worth to underline that in the absence of a structured programme of cardio-oncologic vigilance, the great majority of myocarditis events may be overlooked, or misdiagnosed. A recent meta-analysis of randomized clinical trials found that without a proactive surveillance it is not possible to detect significant cardiotoxicity associated with use of anti-PD-1/PD-L1 immunotherapy ( Rahouma et al., 2019 ). The clinical trial reporting system, yet burdened by sometimes-misleading definitions, also strongly relies on investigator judgment for reporting adverse events.…”
Section: Introductionmentioning
confidence: 99%